Water excess in different soils and sowing times for sunflower in the state of Rio Grande do Sul, Brazil - Lucas, Dionéia Daiane Pitol; Heldwein, Arno Bernardo; Maldaner, Ivan Carlos; Trentin, Roberto; Hinnah, Fernando Dill; Silva, Jocélia Rosa da (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to identify sowing dates with the lowest average occurrence of days with water excess for sunflower crop, and to determine the persistence of consecutive days with water excess considering the available water storage capacity of different soils of the central region of the state of Rio Grande do Sul, Brazil. Crop development and root system deepening were simulated based on thermal summation for 14 sowing dates, from August until mid‑February, with data from 1968 to 2011. From the available water storage capacity of the different soil classes of the region, the sequential daily water balance was calculated to determine the days with water excess. The occurrence of days with water excess was evaluated in different crop development sub‑periods, and exploratory analysis with box‑plot graphs was performed to determine the persistence of consecutive days with water excess during the crop cycle. Water excess limits sunflower cultivation in some areas and periods in the central region of the state of Rio Grande do Sul. The persistence of consecutive days with water excess and the duration of the crop development cycle are influenced by the sowing date.